Ω-Hydroxylation of epoxy- and hydroxy-fatty acids by CYP94AI: possible involvement in plant defence. (December 2000) - Pinot, F.; Skrabs, M.; Compagnon, V.; Salaun, J.-P.; Benveniste, I.; Schreiber, L.; Durst, F.
Abstract : The C18 fatty acid derivatives 9, 10-epoxystearic acid and 9, 10-dihydroxystearic acid were hydroxylated on the terminal methyl by microsomes of yeast expressing CYP94A1 cloned from Vicia sativa. The reactions did not occur in incubations of microsomes from yeast transformed with a void plasmid or in the absence of NADPH. After incubation of a synthetic racemic mixture of 9, 10-epoxystearic acid, the chirality of the residual epoxide was shifted to 66:34 in favour of the 9 S, 10 R enantiomer. Both the 9 S, 10 R and 9 R, 10 S enantiomers were incubated separately. We determined respective K m and V max values of 1.2±0.1 μM and 19.2±0.3 nmol/min per nmol of cytochrome P450 for the 9 R, 10 S enantiomer and of 5.9±0.1 μM and 20.2±1.0 nmol/min per nmol of cytochrome P450 for the 9 S, 10 R enantiomer. This demonstrated that CYP94A1 is enantioselective for the 9 R, 10 S, which is preferentially formed in V. sativa microsomes. Cutin analysis of V. sativa seedlings revealed that it is mainly constituted of derivatives of palmitic acid, a C16 fatty acid. Our results suggest that CYP94A1 might play a minor role in cutin synthesis and could be involved in plant defence. Indeed, 18-hydroxy-9, 10-epoxystearic acid and 9, 10, 18-trihydroxystearic acid have been described as potential messengers in plant-pathogen interactions.